2018
DOI: 10.1017/s0960258518000272
|View full text |Cite
|
Sign up to set email alerts
|

Pollen limitation and its effect on seed germination

Abstract: In nature, fruit and seed production in many plants have been shown to be pollen limited. Pollen limitation is demonstrated when open-pollinated plants that are hand-supplemented (Ps) with outcross pollen produce more fruits and/or seeds than open-pollinated controls that are not hand-pollinated (Po). There are three categories of results in such studies: Ps> Po, Ps= Poand Ps< Po, in which case pollen limitation indices are positive, zero and negative, respectively. In an index widely used to calculate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…Only a small percentage of the numerous studies on pollen limitation have measured the germination responses of seeds from treatment vs control, and some of them showed that pollen supplementation increased seed germination percentage. Of 30 cases (18 species) reviewed by Baskin and Baskin (2018) that compared germination of seeds produced by P s and P o plants, P s > P o in 12, P s = P o in 11 and P s < P o in 7. Thus, based on relative performance (see Appendix), in 40% of the cases pollen supplementation enhanced germination percentages/rate (speed).…”
Section: Influence Of Paternal Parent On Seed Germinationmentioning
confidence: 99%
“…Only a small percentage of the numerous studies on pollen limitation have measured the germination responses of seeds from treatment vs control, and some of them showed that pollen supplementation increased seed germination percentage. Of 30 cases (18 species) reviewed by Baskin and Baskin (2018) that compared germination of seeds produced by P s and P o plants, P s > P o in 12, P s = P o in 11 and P s < P o in 7. Thus, based on relative performance (see Appendix), in 40% of the cases pollen supplementation enhanced germination percentages/rate (speed).…”
Section: Influence Of Paternal Parent On Seed Germinationmentioning
confidence: 99%
“…We calculated the pollen limitation index (PL) as PL = (P s − P o )/P max (P s or P o ) [48], where P s is the number of seeds from pollen-supplemented flowers, P o is the number of seeds from open-pollinated flowers, and P max is the larger of the two values (P s or P o ). For all subsequent analyses, similarly to Larson and Barrett [11], we established zero as the lower boundary of the PL, because any negative indices likely resulted from a potential experimental error [49], and therefore are not meaningful in the context of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The closer PL is to 1, the greater the benefit of pollen supplementation, and the closer PL is to -1 the greater the benefit of open pollination without pollen supplementation. Follwing Baskin and Baskin (2018): (1) when PL is ≥0.10, the plant is pollen limited (P s > P o ), (2) when PL is ≤ -0.10, open pollination is superior to pollen supplementation (P s < P o ) and (3) when PL is between -0.10 and 0.10, they are equal (P s = P o ). PL was 0.23 (A. utahensis), 0.29 (A. scaphoides), 0.33 (A. tragacantha), 0.40 (A. exscapus), 0.41 (A. peckii) and 0.46 (A. brauntonii) for fruit set, which means all six species were pollen limited, i.e.…”
Section: Pollen Limitationmentioning
confidence: 99%